The role of the ketogenic diet in the treatment and prevention of diseases: A literature review - Barański, Dawid; Skwara, Julia; Salińska, Anna; Wasilewski, Marcin; Węgrzyn, Konstancja; Nowicki, Maciej; Laskowski, Gustaw; Góra, Agnieszka; Węgrzyn, Piotr; Dąbrowska, Natalia (Quality in Sport, 2024)
In recent years the ketogenic diet (KD) has become more and more popular. This diet is used not only to reduce weight but also there are an increasingly amount of new researches with multiple possitives effects in some diseases, such as prevention in cardiovascular conditions, diabetes mellitus, obstructive sleep apnea syndrome, some types of cancers and psoriasis. This paper offers an overview of these various medical conditions in which ketogenic diet can be used. Furthermore we describe the mechanism and potential efficacy of the KD. The PubMed and Google Scholar databases were searched.